Analisis Pengaruh Leverage Terhadap Profitabilitas Pada BPR Di NTT Yang Terdaftar Di OJK Periode 2017-2021 - Florianus Muda (AKSIOMA : Jurnal Manajemen, 2024)
This study aims to determine whether the effect of Leverage, as measured by Debt to Asset Ratio and Debt to Equity Ratio, affects Profitability in BPRs in East Nusa Tenggara and has been registered with the Financial Services Authority. The sample used was 93 BPRs that met the criteria for this study. This study uses multiple linear regression analysis where overall, the two Leverage ratios significantly affect Profitability. However, when analyzed separately, there is no significant effect of Debt to Asset Ratio on Profitability, while a significant effect occurs on Debt to Equity Ratio on Profitability.